Moral education in America's schools : the continuing challenge - Hunt, Thomas C., 1930-; Mullins, Monalisa (Emerald Publishing Limited : Information Age Pub., 2005)
This book is not a comprehensive history of moral education in American schools. Rather, it is an episodic history that deals with selected periods, movements, and individuals throughout the course of American education history from the time of colonial Massachusetts in the 17th century up to present times. It is almost entirely devoted to public schools. It is a tale that is fraught with friction and controversy, even legal challenge. Given the nature of the topic, and the passion with which it has been and is currently viewed, it will ever be thus.